Data for: Wolverine density distribution reflects past persecution and current management in Scandinavia ... - Moqanaki, Ehsan; Milleret, Cyril; Dupont, Pierre; Brøseth, Henrik; Bischof, Richard (Dryad, 2023)
After centuries of intense persecution, several large carnivore species in Europe and North America have experienced a rebound. Today's spatial configuration of large carnivore populations has likely arisen from the interplay between their ecological traits and current environmental conditions, but also from their history of persecution and protection. Yet, due to the challenge of studying population-level phenomena, we are rarely able to disentangle and quantify the influence of past and present factors driving the spatial distribution and density of these controversial species. Using spatial capture-recapture models and a data set of 742 genetically identified wolverines Gulo gulo collected over ½ million km2 across their entire range in Norway and Sweden, we identify landscape-level factors explaining the current population density of wolverines in the Scandinavian Peninsula. Distance from the relict range along the Swedish-Norwegian border, where the wolverine population survived a long history of ... : Details on wolverine Gulo gulo data are provided by Moqanaki, E. et al. (here and here) and additional references are given. In brief, this dataset include wolverine noninvasive genetic sampling data extracted from the Scandinavian large carnivore monitoring database (Rovbase 3.0; www.rovbase.no and www.rovbase.se). Wildlife authorities and volunteers conducted both structured searches and opportunistic sampling of putative wolverine scats and hair on snow throughout the species’ range in Norway and Sweden. The structured search tracks and locations of noninvasive samples were GPS recorded. Samples were then processed and analyzed by two dedicated DNA labs using a number of control measures to minimize genotyping errors. First, samples were analyzed with a Single Nucleotide Polymorphism (SNP)-chip with 96 markers. Second, all individuals were analyzed with 19 microsatellite markers to determine species and identity of wolverine individuals as well as their sex. The dataset contains noninvasive genetic ...